2018
DOI: 10.3390/agronomy8090170
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant Capacity and UPLC-PDA ESI-MS Phenolic Profile of Stevia rebaudiana Dry Powder Extracts Obtained by Ultrasound Assisted Extraction

Abstract: Stevia leaves, which are commonly used as a natural sweetener in food products, have increased in importance for antioxidant delivery due to their high content of phenolic compounds. In this study, the influence of the drying process on stevia leaves, with regards to phenolic content and antioxidant activity during drying kinetics 40 °C for 7 h, was studied. The effect of solvent concentration and extraction time using a 32 factorial design on total phenol content (TPC), and on antioxidant activity of extracts… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 30 publications
(28 citation statements)
references
References 31 publications
(41 reference statements)
1
21
1
Order By: Relevance
“…An analysis [51] of the free amino acids composition of 20 Crocus stigma from different countries (Spain, Italy, Greece, Iran) showed that alanine, proline and aspartic acid were the major amino acids in all tested samples. The differences in the obtained results can be explained by the environmental factors, that affect the plant chemical composition [52][53][54][55].…”
Section: Discussionmentioning
confidence: 99%
“…An analysis [51] of the free amino acids composition of 20 Crocus stigma from different countries (Spain, Italy, Greece, Iran) showed that alanine, proline and aspartic acid were the major amino acids in all tested samples. The differences in the obtained results can be explained by the environmental factors, that affect the plant chemical composition [52][53][54][55].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the drying method for fresh leaves also dramatically affects the PPS extraction (Covarrubias‐Cardenas et al., ; R. Lemus‐Mondaca et al., ; Lemus‐Mondaca, Ah‐Hen, Vega‐Gálvez, Honores, & Moraga, ; Periche et al., ). Among the assayed seven drying processes (sun, freeze, shade, convective, vacuum, infrared, and microwave drying), the freeze and shade drying resulted in the highest TPC, while infrared drying yielded the lowest values (R. Lemus‐Mondaca et al., ).…”
Section: Extraction Of Polyphenol From Stevia Rebaudiana (Bertoni) Lementioning
confidence: 99%
“…This complex absorbs at a maximum of 765 nm and a Cary 60 UV-Vis spectrophotometer (Agilent Technologies, Santa Clara, CA, USA) with quartz cuvettes was used. This method has been previously used by numerous researchers for other matrices [22,23]. Due to the extraction kinetics and the stability of the complex formed, the samples were kept in the dark for 30 min, which is the time necessary for the formation of the blue complex.…”
Section: Folin-ciocalteau Proceduresmentioning
confidence: 99%